Is the quality of life different in single and remarried elderly? - Asieh Moudi; Sholeh Shahinfar; Mohammad Reza Razmara; Hamid Salehiniya (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Due to increasing number of the world population, elderly individual's quality of life (QOL) is a matter of concern and marital status as one of the objective measures of QOL is of paramount importance. This study was done to compare the QOL between single and remarried elderly. MATERIALS AND METHODS: This case-control study was conducted on 200 elderly people in Qaen (Southern Khorasan province), Iran. The research sample consisted of two groups of single and remarried elderly, 100 in each group. A demographic and LEIPAD (an acronym deriving from the name of Leiden and Padua universities) QOL questionnaires were completed by the participants via interview. RESULTS: There was a significant difference between single and remarried elderly groups in the QOL (P < 0.001). Linear regression showed that marital status (P < 0.000), economic situation (P < 001), primary education (P < 0.0002), and diploma (P < 0.030) opposed to the illiterate were significantly related to the QOL. In other words, being married and higher economic situation and education increase the QOL. There was a significant negative correlation between the age (P < 0.000) and QOL. The strongest factor was age. CONCLUSIONS: Marital status, income, and education play an important role in all aspects of QOL in older adults. Thus, being married can be a protective factor against physical, psychological, and social problems in old age. Realizing this issue in consultation process of elderly peoples is recommended.